2020
DOI: 10.5435/jaaosglobal-d-20-00097
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Orthopaedic Surgeon's Attire on Patient Perceptions of Surgeon Traits and Identity: A Cross-Sectional Survey

Abstract: Introduction: In orthopaedic surgery, limited research is available addressing how attire, including white coats (WC) and feminine attire such as skirts, affects patient perceptions. It is unknown how surgeon appearance is associated with identification as a surgeon and perception of clinical skills, nor whether this differs between male and female surgeons. Methods: An image-based survey was offered to all adult patients in four orthopaedic surgeons' sport medicine or foot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
2
1
Order By: Relevance
“…The findings from our study differed greatly from other large-scale studies in other centers, which showed a clear preference for formal office attire over scrubs [10,11,[14][15][16][17]. It would seem that our local patients do not perceive formal office attire to reflect aptitude and professionalism amongst physicians, and in fact, may find that formal office attire reflects less friendliness and poorer empathy.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The findings from our study differed greatly from other large-scale studies in other centers, which showed a clear preference for formal office attire over scrubs [10,11,[14][15][16][17]. It would seem that our local patients do not perceive formal office attire to reflect aptitude and professionalism amongst physicians, and in fact, may find that formal office attire reflects less friendliness and poorer empathy.…”
Section: Discussioncontrasting
confidence: 99%
“…Secondly, the local cultural milieu may also play a role. Geographic variation and differing cultures have been shown to affect patients’ preference for physician attire [ 17 ]. In our local tropical climate, it can be uncomfortable to wear layered clothing and as such, patients may recognize that wearing scrubs is comfortable and practical for the physician.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation